Comprehensive investigation on Lithium batteries for electric and hybrid-electric unmanned aerial vehicle applications - Xiao, Chunwu; Wang, Bin; Zhao, Dan; Wang, Chaohui (Thermal science and engineering progress, 2023)
•Lithium battery technologies and development trends in UAV applications are summarized.•Issues of pure Lithium batteries UAV power systems and corresponding solutions are discussed.•Lithium battery-based hybrid power systems are recommended for small, medium size and high-performance UAVs.•Performance optimizations of hybrid power systems in various UAV applications are reviewed. Unmanned aerial vehicles (UAVs) are very promising and convenient flying devices that can be used to execute various missions in both civil and military areas. Especially, they have incomparable advantages to execute tracking, transportation, and even fighting missions in remote areas or severe environments. For UAV applications, Lithium batteries are the most widely used power supply devices. However, the low energy/power density of Lithium batteries would greatly limit the flight endurance or load capacity of UAVs, respectively. Thus, hybrid power systems including Lithium batteries and other energy sources are recommended for high-performance UAVs. This review presents a comprehensive investigation of Lithium batteries for electric and hybrid-electric UAV applications. The investigation includes Lithium battery technologies and development trends in UAV applications, issues of UAVs powered by pure Lithium batteries, hybrid power systems combining Lithium batteries with other energy sources for solving the issues of the pure Lithium battery power system, topology design of Lithium battery-based hybrid power systems for UAVs, and performance optimization of the Lithium battery-based hybrid power systems in various UAV applications. At last, the recommendations for future research priorities are given, which would be very significant for the research and development of high-performance Lithium battery-based power systems for UAVs.